Robust Microfluidic Integrated Electrolyte‐Gated Organic Field‐Effect Transistor Sensors for Rapid, In Situ and Label‐Free Monitoring of DNA Hybridization. (31st May 2022) - Doumbia, Amadou; Webb, Michelle; Behrendt, Jonathan M.; Wilson, Richard J.; Turner, Michael L.
Abstract: Electrolyte‐gated organic field‐effect transistors (EGOFETs) are subject to intense research for biosensing in fluids. The ability of these devices to quantify a variety of chemical and biological molecules sensitively and selectively, but ex situ, has been widely demonstrated. However, continuous monitoring of analyte‐receptor interactions in real time by EGOFETs, in high demand for practical applications, has rarely been explored. Here, an EGOFET array integrated with a microfluidic device, for real‐time detection of the hybridization of DNA is presented. The integrated devices exhibit highly reproducible electrical performance in the array and can operate under different electrical stresses over > 1 h with 85–96% figures of merit retention. The utility of the devices is demonstrated to detect the hybridization of a complementary target DNA in 10 × 10 −3 m phosphate‐buffered saline (1× PBS) selectively with a temporal resolution of < 1 s in a flow of analyte with no incubation step. The detection time is < 30 s and the relative standard deviation of the sensing reproducibility is < 15% under the target concentration of 100 × 10 −9 m . Abstract : Highly stable microfluidic integrated electrolyte‐gated organic field‐effect transistor array rapidly monitors DNA hybridization in real‐time with high specificity, reproducibility, and temporal resolution (<1s).